Evaluation of water quality in the Pantans de Villa Coastal Wetland, Chorrillos, Peru - Nieto Juárez, Jessica Ivana (2024)
In the present work, the water quality (field parameters, anions, dissolved and total metals) in the Pantanos de Villa coastal wetland  was evaluated in 14 sampling stations by collecting samples of surface water (6), groundwater (4) and springs (4) in two sampling campaigns (January and July-August 2022); the chemical analysis of anions and metals in the samples was realized in an accredited laboratory and the evaluation of water quality was carried out according to the Environmental Quality Standard (ECA) for water of Peruvian legislation. It was determined that categories 3 (Irrigation of Vegetables and Animal Drinking) and 4 (Conservation of the Aquatic Environment) of the ECA for water are applicable to the Pantanos de Villa coastal wetland. Among the parameters that exceeded the ECA for water in a greater number of samples were Electrical Conductivity (100%), Dissolved Oxygen (44,44%), Chlorides (88,89%), Nitrates (59,26%), Dissolved Boron (96,30%), Total Boron (100%), Dissolved Selenium (66,67%) and Total Selenium (77,78%). Selenium and Boron are two metals widely distributed in the Pantanos de Villa coastal wetland, in concentrations that endanger the sustainability of the ecosystem and the conservation objectives as a protected natural area because they bioaccumulate, are persistent and are found at levels that can affect aquatic organisms identified in the wetland such as Ceriodaphnia dubia, Phragmites australis and Anas platyrhynchos.